2010
DOI: 10.1017/s1368980010002211
|View full text |Cite
|
Sign up to set email alerts
|

Exploring overweight, obesity and their behavioural correlates among children and adolescents: results from the Health-promotion through Obesity Prevention across Europe project

Abstract: Objectives: The Health-promotion through Obesity Prevention across Europe (HOPE) project aims to bring the European scientific knowledge on overweight, obesity and their determinants together and use the expertise of researchers across Europe to contribute to tackling the obesity epidemic. Design/subjects/results: This special issue of Public Health Nutrition presents important results from one of the work packages of the HOPE project that aims at gaining and integrating knowledge on the determinants of nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…There is scientific evidence that obesity follows a multifactorial model with three main components: biological, lifestyle and environmental risk factors (Boone-Heinonen et al 2008). In adolescents, overweight is generally caused by a lack of physical activity and unhealthy eating patterns (Moreno and Rodriguez 2007;Rey-Lopez et al 2008;Brug et al 2010;de Gouw et al 2010;Landsberg et al 2010). Knowledge about actual dietary intake and its determinants is essential.…”
Section: Introductionmentioning
confidence: 99%
“…There is scientific evidence that obesity follows a multifactorial model with three main components: biological, lifestyle and environmental risk factors (Boone-Heinonen et al 2008). In adolescents, overweight is generally caused by a lack of physical activity and unhealthy eating patterns (Moreno and Rodriguez 2007;Rey-Lopez et al 2008;Brug et al 2010;de Gouw et al 2010;Landsberg et al 2010). Knowledge about actual dietary intake and its determinants is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a chronic process which is associated with a range of diseases; thus, special attention should be paid to its prevention. Besides being related to metabolic disorders, excessive weight gain during adolescence is also a risk factor for extreme obesity in adulthood [2]. According to Schmidt et al [3], recent socioeconomic changes in Brazil have seen a shift towards obesity among the poor, which is probably related to an increased intake of unhealthy foods.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that regular physical activity and proper diet are important not only for preventing lifestyle-related diseases but also for promoting and maintaining one’s health [1,2,3]. In recent years, dietary supplements have attracted interest in the expectation that the individual or synergistic effects of their components might alleviate social health problems such as metabolic syndromes and stress-induced psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%